Open society unresolved: the contemporary relevance of a contested idea - Royer, Christof ca. 20./21. Jahrhundert; Matei, Liviu (Central European University Press, 2023)
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- Introduction: Open Society Unresolved: Charting the Contested Terrain -- Part I Philosophical and Theoretical Perspectives on Open Society -- Chapter 1 Human Nature and the Open Society -- Chapter 2 In Praise of Coldness: The Open Neighborhood and Its Enemies -- Chapter 3 Against Identity: Individuality as the Foundation of Open Society -- Chapter 4 Empirical Embodiment of Critical Rationalism: Deliberative Theory and Open Society -- Chapter 5 Open Society as an Achievement: Popper, Gaus, and the Liberal Tradition -- Chapter 6 Nozick's Meta-Utopia as an Open Society -- Chapter 7 Hannah Arendt and Literary Pedagogy -- Chapter 8 Can Bergson's Definition of Open Society Be Useful Today? -- Part II National and Regional Perspectives on Open Society -- Chapter 9 The Gender of Illiberalism: New Transnational Alliances against Open Societies in Central and Eastern Europe -- Chapter 10 Open Society Contested: Liberal Universalism versus Autocratic Functionalism in Hong Kong -- Chapter 11 "Sorosoids": Uses of Labeling in Bulgaria -- Chapter 12 An African Background to the Concept of Open Society: Ikenga and Ofo Cultic Figures as Structural Representations of the Enterprising Spirit of the Igbo of Nigeria -- Chapter 13 Imagining the Future of Intelligence in Open Societies: Venturing beyond Secrecy and Scientific Prophecy as Totalitarian Modes of Modernity -- Chapter 14 Open Society in Crisis: Making Sense of Public Health and Expert Advice during Covid-19 -- List of Contributors -- Index -- Back cover.